Treatment of multiple synchronous canine mast cell tumours using intratumoural tigilanol tiglate - Brown, Graham K.; Finlay, Jessica R.; Straw, Rodney C.; Ziea, Joy Y.; Leung, Becky; O'Connell, Kathleen; Thomson, Maurine J.; Campbell, Justine E.; Jones, Pamela D.; Reddell, Paul (Frontiers in Veterinary Science, 2022)
Mast cell tumours (MCTs) are a common canine skin neoplasia. While they generally occur as single tumours, multiple synchronous MCTs (msMCTs) of de novo/non-metastatic origin are reported in a proportion of the patient population. Where there is no evidence of metastasis or lymphatic spread, MCTs are effectively controlled by surgery and other local therapies. However, treatment of de novo msMCTs can be more challenging, especially when they occur in surgically difficult locations. Here we report the use of tigilanol tiglate, a novel small molecule registered as a veterinary pharmaceutical for local treatment of non-metastatic MCTs, in the treatment of patients with msMCTs presenting at three Australian specialist referral centres. We also present a meta-analysis of the literature to provide a better understanding of the prevalence of canine msMCTs. Nine patients with a total of 32 MCTs were treated during the study. A complete response was recorded in 26 (81%) of the individual MCTs on Day 28 after a single tigilanol tiglate injection. Of the 6 initially non-responsive MCTs, one achieved a complete response after a further tigilanol tiglate treatment. A complete response was reported at 6 months in all 22 of the tumours that were evaluable and that had recorded a complete response at Day 84. For the literature meta-analysis, 22 studies were found with prevalence estimates of msMCTs ranging from 3 to 40%; when combined these studies yielded 3745 patients with a prevalence of 13% (95% CI 10; 16). Overall, the results demonstrate the utility of intratumoural tigilanol tiglate as an option for treatment of multiple MCTs where multiple surgical resections would have been required.